Awareness and Knowledge of the Female Athlete Triad and Relative Energy Deficiency in Sport (REDs) among Multi-Specialty Healthcare Professionals - Visagie, Rowena (Division of Forensic Medicine and Toxicology, 2025)
Background The female athlete triad (Triad) and Relative Energy Deficiency in Sport (REDs) are serious conditions with harmful health and athletic performance consequences. International research suggests that awareness and understanding of these terms and their associated repercussions among healthcare professionals is lacking. The awareness and knowledge of the Triad and REDs among healthcare providers in South Africa is unknown. Objective The aim of this study is to investigate the knowledge and awareness of the Triad and REDs, and the comfort of multi-specialty healthcare professionals in diagnosing, treating, and referring individuals with these and related conditions. Methodology An online expert-reviewed questionnaire was designed and distributed to healthcare professionals to assess awareness and knowledge. Results Of the 162 survey participants, 51% were aware of the Triad and 40% were familiar with the term REDs. Of those aware of the Triad, 46% were able to identify all 3 components. Among those familiar with REDs, 69% were able to recognise that low energy availability (LEA) is the main underlying cause, 80% had good knowledge of potential REDs consequences, and 60% were able to correctly identify potential symptoms of REDs. Investigatory practices regarding certain health manifestations including low bone mineral density and menstrual dysfunction were found to be lacking. Overall, 6%, 8% and 44% reported feeling very comfortable diagnosing, treating, and referring those with REDs respectively. Only 14% felt very comfortable diagnosing disordered eating and eating disorders. Conclusion Overall, healthcare professionals have generally poor awareness of the Triad and REDs, as well as low rates of comfort in diagnosing, treating, and referring those with REDs. Education strategies to address the gaps in awareness and knowledge among multi-specialty healthcare providers is warranted.